Potential use of Vibriophage in association with antibiotic to treat the vibrio Cholerae biofilm - Farheen, Saria (Brac University, 2021)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2021.